Presence of Age Restrictions for Children to Have Social Media Accounts in Law Number 27 of 2022 Concerning Personal Data Protection - Diarola Bernike*; Christian Andersen (Universitas Syiah Kuala, 2023)
Social media offers many offers to its users entertainment media, social media, life-styles media, business media, educational media. But despite the many attractions offered on social media there is danger. One social media user is a minor who is particularly susceptible to the dangers on social media. Thus was born the 27th 2022 year law on personal data protection, through which through these invitations it is hoped that children will be under the age of a minor and more fair protection from a child's parents. As for the method of research used in this study is normative-juridical. Studies have been found that birth rules regarding processing and the trial of the child's personal data should be subject to parental consent because the child is still vulnerable to social media hazards. But the application of child supervision in using social media is a challenge in itself because the parent of the child cannot possibly be ignorant of social media, therefore, in addition to the 27 year 2022 act on personal data protection, the child need to be given social media education so that the ease on social media can remain accessible to minors, More than that, a child's process for social media needs to be organized into an even more organized system, such as having a feature as creating an id card photo to join social media.